Miscarriage matters: the epidemiological, physical, psychological, and economic costs of early pregnancy loss. Issue 10285 (1st May 2021) - Quenby, Siobhan; Gallos, Ioannis D; Dhillon-Smith, Rima K; Podesek, Marcelina; Stephenson, Mary D; Fisher, Joanne; Brosens, Jan J; Brewin, Jane; Ramhorst, Rosanna; Lucas, Emma S; McCoy, Rajiv C; Anderson, Robert; et al.
Summary: Miscarriage is generally defined as the loss of a pregnancy before viability. An estimated 23 million miscarriages occur every year worldwide, translating to 44 pregnancy losses each minute. The pooled risk of miscarriage is 15·3% (95% CI 12·5–18·7%) of all recognised pregnancies. The population prevalence of women who have had one miscarriage is 10·8% (10·3–11·4%), two miscarriages is 1·9% (1·8–2·1%), and three or more miscarriages is 0·7% (0·5–0·8%). Risk factors for miscarriage include very young or older female age (younger than 20 years and older than 35 years), older male age (older than 40 years), very low or very high body-mass index, Black ethnicity, previous miscarriages, smoking, alcohol, stress, working night shifts, air pollution, and exposure to pesticides. The consequences of miscarriage are both physical, such as bleeding or infection, and psychological. Psychological consequences include increases in the risk of anxiety, depression, post-traumatic stress disorder, and suicide. Miscarriage, and especially recurrent miscarriage, is also a sentinel risk marker for obstetric complications, including preterm birth, fetal growth restriction, placental abruption, and stillbirth in future pregnancies, and a predictor of longer-term health problems, such as cardiovascular disease and venous thromboembolism. The costs of miscarriage affect individuals, health-care systems, and society. The short-term national economic cost of miscarriage is estimated to be £471 million per year in the UK. As recurrent miscarriage is a sentinel marker for various obstetric risks in future pregnancies, women should receive care in preconception and obstetric clinics specialising in patients at high risk. As psychological morbidity is common after pregnancy loss, effective screening instruments and treatment options for mental health consequences of miscarriage need to be available. We recommend that miscarriage data are gathered and reported to facilitate comparison of rates among countries, to accelerate research, and to improve patient care and policy development.